Effectiveness and optimum level of protected methionine in fattening pig diets - Figueroa-Velasco, José L.; Trujano-San-Luis, David; Martínez-Aispuro, José A.; Sánchez-Torres, María T.; Crosby-Galván, María M.; Ruíz-Flores, Agustín; Cordero-Mora, José L. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Methionine (Met) requirements have not been clearly established for fattening pigs due to their metabolic interrelationships and its bioavailability for protein synthesis. Objective: To determine the optimum level of regular crystalline or protected Met in pig diets from nursery to finishing. Methods: A total of 48 crossbred pigs (11.74±1.72 kg of initial body weight) were used. The treatments consisted of adding four levels (0.00, 0.05, 0.10, 0.15% in addition to dietary content) and two types of Met (regular and protected) to pig diets. Results: Nursery, Finishing I, and II pigs fed protected Met increased daily feed intake (DFI; p≤0.10). Protected Met raised daily weight gain (DWG) in nursery pigs and increased backfat thickness (BT) in nursery and grower pigs (p≤0.10). In Finishing I pigs, protected Met increased DWG and improved carcass characteristics (p≤0.10). In nursery and grower pigs, an extra 0.15% Met decreased feed:gain ratio (FGR; p≤0.10). In grower and Finishing II pigs fed extra 0.05% Met improved DWG and extra 0.10% Met reduced plasma urea concentration (p≤0.10). Conclusions: Feeding protected Met in pig diets increases DWG, DFI and BT. Increasing 0.05-0.15% Met level improves FGR, DWG, potentially reducing nitrogen excretion to the environment.